Pulse propagation through a dielectric slab doped with a triple quantum dot nanostructure. (20th September 2016) - Nasehi, R; Mahmoudi, M; Sahrai, M
Abstract: The propagation of an electromagnetic pulse through a dielectric slab doped with a triple quantum dot (QD) nanostructure has been discussed in the presence of electron tunneling. We include the effect of an incoherent pump field in the transmission and reflection of a pulse in a triple QD. It is shown that the reflected and transmitted pulses can be switched from subluminal to superluminal light propagation by changing either the rate of the incoherent pump field or the inter-dot tunneling between QD1, QD2 and QD3 in a slab. Furthermore, it is demonstrated that the inter-dot tunnel coupling can significantly affect the behavior of optical bistability (OB) and optical multi-stability (OM) in a dielectric slab. The obtained results can be used for the development of new types of nanoelectronic devices for realizing the switching process.